PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK ACCU YUASA YANG DIPROMOSIKAN DISTRIBUTOR PT RIAU INDOTAMA ABADI di BATAM - Yola Putri Ningsih; Shinta Wahyu Hati (Politeknik Negeri Batam, 2017)
The research aims to determine the influences of promotion mix to the purchase decision of product Accu Yuasa at PT Riau Indotama Abadi. This research used explanatory research method to 79 wholesalaers and repair shops to cooperate with PT Riau Indotama Abadi in Batam. From the results of multiple regression, showed there was partially effect of sales promotion variable on purchase decision of product Accu Yuasa around 0.345, there was partially effect of public relation variable on purchase decision of product Accu Yuasa around 0.357, there was partially effect of direct marketing variable on purchase decision of product Accu Yuasa around 0.364. As for the variable advertising and personal selling not partially effect on purchase decision of product Accu Yuasa. And there is a simultaneous effect of variable advertising, sales promotion, personal selling, public relations and direct marketing on purchase decision of product Accu Yuasa.